Some Properties of Multiplication Modules - Hamid Tavallaee; Robabeh Mahtabi (IndoMS, 2017)
Let M be an R-module. The module M is called multiplication if for anysubmodule N of M we have N = IM, where I is an ideal of R. In this paperwe state some basic properties of multiplication modules.